Improved survival with MEK inhibition in BRAF-mutated melanoma - Flaherty, Keith T.; Hassel, Jessica C.; Utikal, Jochen (The New England journal of medicine, 2012)
About 160,000 new cases of melanoma are diagnosed and 48,000 melanoma-related deaths occur worldwide each year.1 Among cancers in patients under 40 years of age, the incidence of melanoma is second only to that of breast cancer for women and leukemia for men.2 Before 2010, no systemic therapy had been shown to improve overall survival among patients with metastatic melanoma, and only modest improvements were observed with interferon as an adjuvant drug.3 Ipilimumab, a monoclonal antibody targeting cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4), and vemurafenib, a selective BRAF inhibitor, have both been shown to improve survival among patients with metastatic melanoma . . .
Gesehen am 21.08.2019